2016
DOI: 10.1590/1807-1929/agriambi.v20n2p169-173
|View full text |Cite
|
Sign up to set email alerts
|

Stability of cactus-pear powder during storage

Abstract: A B S T R A C TThe stability of cactus-pear powder, obtained by the process of spray drying for 40 days, was evaluated under controlled conditions of relative air humidity (83%) and temperature (25 and 40 °C). The whole pulp was characterized with regard to its physico-chemical parameters: pH, total titratable acidity, soluble solids, water content, total solids, ashes, reducing sugars, total sugars, non-reducing sugars, luminosity, redness, yellowness and water activity. The stored samples in powder were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
8
0
4
Order By: Relevance
“…Between the temperatures (30 and 40 º C), the moisture content did not differ from time zero to 45 days of storage, except at the time of 60 days, when the sample stored at temperature of 40 º C showed higher moisture content compared with that at 30 º C. Galdino et al (2016) analyzed cactus-pear powder stability, at temperatures of 25 and 40 º C, and reported that moisture content significantly increased along the storage time for the studied temperatures, and such increment was more evident at 40 °C, from the period of 10 days on, indicating that temperature significantly influenced moisture absorption. Hygroscopic characteristics of foods depend mainly on their chemical composition and storage conditions (temperature and relative air humidity) (Arlindo et al, 2007).…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 81%
See 1 more Smart Citation
“…Between the temperatures (30 and 40 º C), the moisture content did not differ from time zero to 45 days of storage, except at the time of 60 days, when the sample stored at temperature of 40 º C showed higher moisture content compared with that at 30 º C. Galdino et al (2016) analyzed cactus-pear powder stability, at temperatures of 25 and 40 º C, and reported that moisture content significantly increased along the storage time for the studied temperatures, and such increment was more evident at 40 °C, from the period of 10 days on, indicating that temperature significantly influenced moisture absorption. Hygroscopic characteristics of foods depend mainly on their chemical composition and storage conditions (temperature and relative air humidity) (Arlindo et al, 2007).…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 81%
“…Han et al (2016) also observed no alterations in the mushroom powder stored at temperatures of -20, 4, 25 and 35 º C, for 9 months, claiming that for a food to have prolonged shelf life, it is necessary to control acidity, pH and water activity level. Galdino et al (2016) stored cactus pear powders at temperatures of 25 and 40 °C, and reported that the mean values of total titratable acidity of samples stored at both temperatures underwent small oscillations along the storage time. However, in general, the authors claimed that the samples did not undergo significant alterations, indicating that there was no evidence of microbiological contamination.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…Os resultados encontrados por Galdino et al, (2016) 4 diminuíram e aumentaram nos tempos 5 e 6 que se igualaram aos tempos 0 e 1. Este aumento do pH nos últimos dias de armazenamento dos pós pode ser um indicativo de que as amostras estavam em processo de decomposição por hidrólise ou oxidação ou fermentação os quais podem alterar a concentração de íons de hidrogênio e a sua acidez (Alexandre et al, 2014).…”
Section: Figuraunclassified
“…Já Alexandre et al (2014) observaram comportamento inverso ao trabalharem com pitanga em pó acondicionada em embalagem plástica, em que, apresentou um decréscimo de intensidade vermelho de ± 30% no final de 60 dias de armazenamento. Galdino et al (2016) em seu experimento com pó de fígo-da-índia, desidratado em spray-dryer obtiveram redução da coordenada a* com 35% de maltodextrina, armazenado em embalagens laminadas, a uma temperatura de 25ºC e período de 40 dias. Já Oliveira et al (2015) no pó do fruto de mandacaru, desidratado em spray dryer com 10% de maltodextrina DE (10), armazenado em embalagens laminadas, por um período de 50 dias, relataram também redução da cor a*.…”
Section: Estádiosunclassified
“…There are several studies seeking to understand the stability of food products during their storage, such as Galdino et al (2016), studying the stability of cactus pear (Opuntia ficus-indica) powder, Conegero et al (2017), studying 'mangaba' (Hancornia speciosa Gomes) pulp powder, Rodrigues et al (2018) evaluating a byproduct of 'jabuticaba' (Plinia cauliflora) stored in microcapsules, and Sousa et al (2016) evaluating the stability of cashew (Anacardium occidentale L.) juice powder dehydrated in a spouted bed.…”
mentioning
confidence: 99%